Miniaturization of hiPSC-derived 3D neural cultures in stirred-tank bioreactors for parallelized preclinical assessment of rAAV - Gomes, Catarina M.; Sebastião, Maria João; Silva, Gabriela; Moura, Filipa; Simão, Daniel; Gomes-Alves, Patrícia; Alves, Paula M.; Brito, Catarina (Frontiers in Bioengineering and Biotechnology, 2024)
Engineered 3D models employing human-induced pluripotent stem cell (hiPSC) derivatives have the potential to recapitulate the cell diversity and structure found in the human central nervous system (CNS). Therefore, these complex cellular systems offer promising human models to address the safety and potency of advanced therapy medicinal products (ATMPs), such as gene therapies. Specifically, recombinant adeno-associated viruses (rAAVs) are currently considered highly attractive for CNS gene therapy due to their broad tropism, low toxicity, and moderate immunogenicity. To accelerate the clinical translation of rAAVs, in-depth preclinical evaluation of efficacy and safety in a human setting is primordial. The integration of hiPSC-derived CNS models in rAAV development will require, amongst other factors, robust, small-scale, high-throughput culture platforms that can feed the preclinical trials. Herein, we pioneer the miniaturization and parallelization of a 200 mL stirred-tank bioreactor-based 3D brain cell culture derived from hiPSCs. We demonstrate the applicability of the automated miniaturized Ambr® 15 Cell Culture system for the maintenance of hiPSC-derived neurospheroids (iNSpheroids), composed of neuronal and glial cells. Critical process parameters were optimized, namely cell density and agitation mode. Under optimized conditions, stable iNSpheroid cultures were attained in the microbioreactors for at least 15 days, with high cell viability and astrocytic and neuronal phenotype maintenance. This culture setup allowed the parallelization of different rAAVs, in different multiplicities of infection (MOI), to address rAAV-host interactions at a preclinical scale. The iNSpheroids were exposed to rAAV2-and rAAV9-eGFP in the microbioreactors. Transgene expression was detected 14 days post-transduction, revealing different astrocyte/neuron tropism of the two serotypes. We advocate that the iNSpheroid cultures in miniaturized bioreactors are reliable and reproducible screening tools for addressing rAAV transduction and tropism, compatible with preclinical demands.